2022
DOI: 10.3389/fvets.2022.1064433
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between autophagy and apoptosis during pseudorabies virus infection

Abstract: Both autophagy and apoptosis are mechanisms that maintain homeostasis in cells and that play essential roles in viral infections. Previous studies have demonstrated that autophagy and apoptosis pathways occurred with complex relationships in virus-infected cells. However, the regulation between these two processes in Pseudorabies virus (PRV) infection remains unclear. In the present study, we demonstrated that activated autophagy was induced at the early stage of PRV infection and that apoptosis was induced at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Generally, apoptosis is activated mainly in the late stage of infection by PRV. Moreover, studies have shown that PRV triggers ROS production and causing of apoptosis in autophagic-damaged cells, which indicated that ROS may be participated in the linking of autophagy and apoptosis in cells infected by PRV [15]. Oxidative stress is associated with various cell death processes, including apoptosis, caused by viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, apoptosis is activated mainly in the late stage of infection by PRV. Moreover, studies have shown that PRV triggers ROS production and causing of apoptosis in autophagic-damaged cells, which indicated that ROS may be participated in the linking of autophagy and apoptosis in cells infected by PRV [15]. Oxidative stress is associated with various cell death processes, including apoptosis, caused by viral infection.…”
Section: Discussionmentioning
confidence: 99%